2014
DOI: 10.3171/2014.2.peds13527
|View full text |Cite
|
Sign up to set email alerts
|

Isolated unilateral rupture of the alar ligament

Abstract: Only 6 cases of isolated unilateral rupture of the alar ligament have been previously reported. The authors report a new case and review the literature, morbid anatomy, and pathogenesis of this rare injury. The patient in their case, a 9-year-old girl, fell head first from a height of 5 feet off the ground. She presented with neck pain, a leftward head tilt, and severe limitation of right rotation, extension, and right lateral flexion of the neck. Plain radiographs and CT revealed no fracture but a shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 15 publications
(29 reference statements)
0
18
0
10
Order By: Relevance
“…Inter-fragmentary compression pressure alone cannot guarantee the biomechanical superiority of the Herbert screw compared with the cannulated lag screw. Second, clinically, greater inter-fragmentary compression pressure may not mean greater reduction of the fracture gap in odontoid process fixation, because, in humans, the dens is attached by many strong ligaments including apical and alar ligaments 12 , 26) . Furthermore, because there are so many risk factors of fusion failure of odontoid process fixation 2 , 3 , 11 , 15) , we must consider other factors for higher bone fusion rates after odontoid screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-fragmentary compression pressure alone cannot guarantee the biomechanical superiority of the Herbert screw compared with the cannulated lag screw. Second, clinically, greater inter-fragmentary compression pressure may not mean greater reduction of the fracture gap in odontoid process fixation, because, in humans, the dens is attached by many strong ligaments including apical and alar ligaments 12 , 26) . Furthermore, because there are so many risk factors of fusion failure of odontoid process fixation 2 , 3 , 11 , 15) , we must consider other factors for higher bone fusion rates after odontoid screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, isolated rupture of the alar ligament has been managed conservatively with external immobilization, suggesting that other isolated ligamentous injuries may be treated with this approach [25]. Typically, unless frank AOD is seen on imaging, patients without neurological deficits may be treated conservatively [21, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical symptoms were reported in patients with WAD and AL signal alterations. [16][17][18]39 However, the clinical significance of these signal changes has been disputed since the 1990s: various MRI studies showed that there is a broad range of variations in interindividual signal intensity and morphology in AL, both in patients with WAD [36][37][38][39][40] and healthy volunteers. 23,24,29 As a cautionary note, MRI should generally be accompanied in WAD, and especially in suspected upper spinal instability, with multimodal imaging procedures depending on the clinical setting of the patient.…”
Section: Discussionmentioning
confidence: 99%